Realigning Risk and Enhancing Liability Frameworks for Design Errors in Traditional Construction Contracts: A Comparative Study of the UAE and Oman - AL GHASSANI, KHAWLAH SAID AHMED (2025)
The use of design liability frameworks in construction contracts is an important aspect in the management of risks, financial security, and the understanding of the contracts. This dissertation aims to explore design liability frameworks in traditional construction contracts, especially in the UAE (FIDIC Red Book 2017) and Oman (Standard Conditions 2019). The study reviews legal frameworks, risk distribution, indemnity insurance provisions, dispute resolution mechanisms, and how the inclusion of technologies such as BIM, AI, and VR affects contractual obligations. The study reveals some distinctions between the UAE and Oman in terms of risk management, the roles and responsibilities of the stakeholders, and the enforcement of liabilities. The findings show that both legal systems need to be developed further. Based on the findings of this research, the dissertation provides legal and contractual recommendations that can be used to increase the level of financial security, risk management, and legal flexibility in terms of the new forms of construction management. Potential topics for future research include comparing the situations in other countries, studying specific case studies of design liability conflicts, and proposing new approaches to liability management with the help of artificial intelligence. Thus, the problems identified can be solved, and the design liability provisions in the UAE and Oman can be improved to reduce the legal uncertainties, improve the financial efficiency of construction projects, and enhance the efficiency of contract management in the construction industry.